Liquid dynamics in response to an impinging low-temperature plasma jet. (14th December 2018) - Brubaker, T R; Ishikawa, K; Kondo, H; Tsutsumi, T; Hashizume, H; Tanaka, H; Knecht, S D; Bilén, S G; Hori, M
Abstract: The liquid-phase behavior induced by an atmospheric pressure plasma jet impinging onto water-based solutions was experimentally investigated. An increase in cavity size and circulation size resulting from an increase in impact force of the plasma jet with respect to a helium gas jet were observed through particle image velocimetry and cavity measurements. The increase in circulation size due to plasma discharge was larger than the increase solely due to an increase in jet impact force, suggesting additional shear along the liquid free surface evidenced by schlieren images of plasma-induced gas flow adherence after impingement. Liquid evaporation rate increased and mean liquid temperature decreased due to plasma effects on jet behavior. Plasma-induced decreases in liquid pH and temperature were contained within the circulation flow, leading to strong pH and temperature gradients within the liquid volume. Areas treated by the jet became acidic and remained more acidic than other portions of the liquid due to circulation vortices, highlighting the consequences of jet and liquid vessel parameters for plasma jet-liquid applications.